(untitled) (Scientific journal of the Fergana State University, 2023)
This article researches the determination of the level of influence of risks arising in service sector enterprises, the division of their impact into groups depending on the negative or positive result, as well as the division of the levels of risk exposure into zones. At the same time, an algorithm was developed to improve the efficiency of enterprises based on a risk management system.